Pendampingan Kelompok Tani Manise Memanfaatkan Hama Keong Mas (Pomacea sp) Sebagai Pakan Ikan Gurame (Osphronemus gouramy) - Silaban, Saronom; Rajagukguk, Juniastel; Simorangkir, Murniaty (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2021)
The high price of chemical fish feed is a serious problem for “Tani Manise" group partners in Sari Rejo village, Medan Polonia sub-district. The reality in the field shows that the presence of golden snail (Pomace sp) in partner locations has not been utilized properly as raw material for organic feed for gurame fish (Osphronemus gouramy). The purpose of this community partnership program (PKM) activity is to assist partners in problems solving faced with the use of the golden snail as organic feed for gurame fish which has economic value and contains good nutrition. To solve the problems faced by partners, an approach is used with planning methods, training and mentoring. The results of PKM activities show that giving organic feed made from golden snail flour can accelerate the growth of gurame fish from the previous 25.0 g / month to 33.3 g / month. There is an increase in growth of about 8.3 grams per month. The high cost of feed can be reduced to 9,000 / kg using organic feed, while the chemical based fish feed is in the range of 13,000 / kg. The implementation of PKM activities can reduce high production costs, accelerate the growth of gurame fish, and the ability of partner human resources in processing raw material for golden snail pests into organic feed containing good nutrition.